PENGARUH KUALITAS PELAYANAN DAN MOTIVASI KERJA TERHADAP SOFT SKILL TUTOR PKBM MELATI INDAH - M Sofyan Wardana; Muhammad Fauzan; Agus Maulana (Indragiri Research Center (ingreat), 2026)
This study aims to analyze the effect of service quality and work motivation on the soft skills of tutors at PKBM Melati Indah. The background of this research is based on the importance of soft skills in supporting the quality of non-formal education services, as well as the existing problems related to communication skills, teamwork, and self-confidence of tutors. This research uses a quantitative approach with a descriptive associative method. The population consists of all tutors at PKBM Melati Indah, totaling 30 respondents, using a total sampling technique. Data were collected through Likert-scale questionnaires and analyzed using validity tests, reliability tests, and multiple linear regression analysis with the help of SPSS. The results show that service quality has a positive and significant effect on soft skills, with a t-value of 2.644 > t-table of 2.048 and a significance value of 0.013 < 0.05. Meanwhile, work motivation does not have a significant partial effect, with a t-value of 1.242 < t-table of 2.048 and a significance value of 0.225 > 0.05. Simultaneously, both variables have a significant effect on soft skills, with an F-value of 14.138 > F-table of 3.354 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 0.512, indicating that 51.2% of soft skills are influenced by service quality and work motivation. In conclusion, service quality plays an important role in improving tutors’ soft skills, while work motivation does not have a significant partial effect.